IMPLEMENTASI STRATEGI PEMBELAJARAN CONTEXTUAL TEACHING LEARNING (CTL) PADA MATA PELAJARAN AL-QUR’AN HADIS KELAS IX-SAINS B DI MADRASAH ALIYAH NEGERI 1 MEDAN - Malika Amilia Rahman; Sufiani; Andreo Diwa Arsenta; Arlina (STKIP Subang, 2025)
This study aims to describe the implementation of the Contextual Teaching and Learning (CTL) instructional strategy in the Al-Qur’an and Hadith subject for Grade IX Science B at Madrasah Aliyah Negeri 1 Medan and to identify its effects on students’ activeness, motivation, and understanding. The study adopts a qualitative approach using a phenomenological research design. Data were collected through direct classroom observations of the learning process, interviews with the Al-Qur’an and Hadith teacher and students, and document analysis. Data credibility was ensured through prolonged engagement, persistent observation, negative case analysis, and triangulation of sources and techniques. The findings indicate that the implementation of the CTL strategy has a positive impact on the learning process. Students appeared more active, enthusiastic, and engaged in discussions, question-and-answer sessions, and group presentations. Learning became more meaningful as the material on halal and thayyib food was connected to students’ real-life experiences, such as the types of food they consume in their daily lives. The CTL strategy also contributed to enhancing students’ learning motivation and critical thinking skills. Although some challenges were identified, such as a few students’ limited participation, overall the CTL strategy was successful in creating an active, collaborative, and real-life–relevant learning environment for students.